Estimation of Synaptic Conductances in Presence of Nonlinear Effects Caused by Subthreshold Ionic Currents - Vich, Catalina; Berg, Rune W.; Guillamon, Antoni; Ditlevsen, Susanne (Frontiers in Computational Neuroscience, 2017)
Subthreshold fluctuations in neuronal membrane potential traces contain nonlinear components, and statistical inference can be poor if linear models are employed to estimate synaptic conductances. We propose a new strategy to estimate synaptic conductances, which has been tested using in silico data and applied to in vivo recordings. The model is constructed to capture the non-linearities caused by subthreshold activated currents, and the estimation procedure can discern between excitatory and inhibitory conductances using only one membrane potential trace. More precisely, we perform second order approximations of biophysical models to capture the subthreshold non-linearities, resulting in quadratic integrate-and-fire models, and apply approximate maximum likelihood estimation where we only suppose that conductances are stationary in a $50-100\,ms$ time window. The results show an improvement compared to existent procedures for the models tested here